IMPLEMENTASI TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) DALAM INOVASI PEMBELAJARAN DIGITAL DI SEKOLAH MENENGAH PERTAMA SYUBBANUL WATHON TEGALREJO - Aini, Siti Nur; Athi, Fina Umu Rif (Institut Agama Islam Syubbanul Wathon Magelang, 2025)
This research examines the implementation of Information and Communication Technology (ICT) in digital learning innovations at SMP Syubbanul Wathon Tegalrejo. The study aims to evaluate how ICT can enhance educational practices, engage students, and improve learning outcomes. The methodology includes qualitative data collection through interviews with educators and students, as well as classroom observations. The results reveal that the integration of ICT in teaching methods significantly increases student motivation and participation. Various tools, such as online platforms and multimedia resources, are utilized to create a dynamic learning environment that caters to diverse learning styles. However, the study also identifies several challenges faced by the institution, including inadequate infrastructure, limited access to technology, and the necessity for ongoing professional development for teachers. Addressing these challenges is crucial for maximizing the benefits of ICT in education. The findings suggest that with proper training and resources, teachers can effectively harness ICT to facilitate collaborative learning and critical thinking among students. Furthermore, the research highlights the importance of continuous evaluation and adaptation of ICT strategies to meet the evolving needs of learners. In conclusion, the successful implementation of ICT in SMP Syubbanul Wathon Tegalrejo demonstrates its potential to transform traditional educational practices and foster an innovative learning culture.